Activity of Lenalidomide in MDS Tied to Degradation of CSNK1A1 - Vinall, Maria (MD Conference Express, 2014)
This study identifies a potential mechanism of action for lenalidomide in del(5q) myelodysplastic syndrome and identifies a single nonconserved amino acid in mice and humans that determines lenalidomide susceptibility. The results may facilitate the development of improved preclinical models and reinforces the importance of haploinsufficient genes in the pathogenesis and treatment of disease.